Modified Subcutaneous Buried Horizontal Mattress Suture Compared With Vertical Buried Mattress Suture. Issue 2 (August 2017) - Meng, Fanjun; Andrea, Sisti; Cheng, Shenling; Wang, Qiang; Huo, Ran
Abstract : Background: Wound tension reduction is still a challenge to surgeons. Over the years, many techniques have been proposed to avoid this issue. In this paper, we present a new suture technique. Objectives: To investigate the tension-reduction effectiveness of the modified subcutaneous buried horizontal mattress suture compared with the vertical buried mattress suture technique. Methods: Two suture techniques, the vertical buried mattress suture (group A) and the modified subcutaneous buried horizontal mattress suture (group B), were performed on paired samples of symmetrical skin flaps. An equal pulling force was applied to each paired sutured flap, and the dehiscences of the samples in the two groups were compared. Then, after the periodic mechanical pulling force was recorded, the dehiscences were compared again. Results: The dehiscences of the vertical buried mattress suture samples (group A) were much wider than their corresponding samples. Modified subcutaneous buried horizontal mattress suture samples (group B) remained well closed with no or minimal dehiscence, under various tensions, even after mechanical pulling force was applied. Conclusion: The modified subcutaneous buried horizontal mattress suture greatly decreased the tension on the dermis and subcutaneous tissue in our in vitro experiment.